Rapid HIV Testing at Gay Pride Events to Reach Previously Untested MSM: U.S., 2009–2010. (July 2014) - Mdodo, Rennatus; Thomas, Peter E.; Walker, Anissa; Chavez, Pollyanna; Ethridge, Steven; Oraka, Emeka; Sutton, Madeline Y.
We offered rapid HIV testing at social events frequented by young men who have sex with men (MSM), a group disproportionately affected by the HIV epidemic. We tested 1, 312 MSM; of those MSM, 1, 072 (81.7%) reported HIV testing history. Of those reporting HIV testing history, 550 (51.3%) were non-Hispanic black and 404 (37.7%) were aged <25 years. One hundred twenty-eight (11.9%) had never tested for HIV; 77 (7.2%) were preliminarily positive, with 15 (19.5%) being first-time testers. Factors associated with no previous HIV test included young age (13–24 years) (adjusted odds ratio [AOR] = 3.5, 95% confidence interval [CI] 1.9, 6.5) and non-Hispanic black (AOR=3.2, 95% CI 1.6, 6.4) or Hispanic (AOR=2.8, 95% CI 1.2, 6.3) race/ethnicity. HIV testing at Gay Pride events reaches young, previously untested MSM. This venue-based HIV testing approach at nonclinical sociocultural events is an additional strategy for HIV prevention goals to increase the number of people aware of their HIV infection with subsequent linkage to HIV care.